Chronic Inflammation in Obesity and the Metabolic Syndrome - Rosário Monteiro; Isabel Azevedo (Hindawi Limited, 2010)
The increasing incidence of obesity and the metabolic syndrome is disturbing. The activation of inflammatory pathways, used normally as host defence, reminds the seriousness of this condition. There is probably more than one cause for activation of inflammation. Apparently, metabolic overload evokes stress reactions, such as oxidative, inflammatory, organelle and cell hypertrophy, generating vicious cycles. Adipocyte hypertrophy, through physical reasons, facilitates cell rupture, what will evoke an inflammatory reaction. Inability of adipose tissue development to engulf incoming fat leads to deposition in other organs, mainly in the liver, with consequences on insulin resistance. The oxidative stress which accompanies feeding, particularly when there is excessive ingestion of fat and/or other macronutrients without concomitant ingestion of antioxidant-rich foods/beverages, may contribute to inflammation attributed to obesity. Moreover, data on the interaction of microbiota with food and obesity brought new hypothesis for the obesity/fat diet relationship with inflammation. Beyond these, other phenomena, for instance psychological and/or circadian rhythm disturbances, may likewise contribute to oxidative/inflammatory status. The difficulty in the management of obesity/metabolic syndrome is linked to their multifactorial nature where environmental, genetic and psychosocial factors interact through complex networks.